دور النشاط الرياضي الترويحي في التقليل من الضغوط النفسية لدى تلاميذ شهادة التعليم المتوسط - مداحي, احمد; مخلش, عمر (institut d’éducation sportive et physique / Université de Mostaganem, 2021)
ملخص الدراسة تهدف هذه الدراسة إلى الكشف عن العلاقة القائمة بين النشاط البدني الترويحي والضغط النفسي لدى تلاميذ السنة الرابعة متوسط قوامهم 60 تلميذا، وباستخدام المنهج الوصفي إلارتباطي وبالاعتماد على مقياس الضغط النفسي، وعلى ضوء المعالجة الإحصائية لفرضيات الدراسة للتأكد من تحققها وعدم تحققها، فإننا وبعد تحليلنا وعرضنا ومناقشتنا لنتائج جداول الدراسة نستنتج على أنه: - للنشاط البدني الرياضي التربوي دور في التقليل من الضغوطات النفسية لدى تلاميذ التعليم المتوسط. وقد تحققت كل الفرضيات الجزئية: - للنشاط الترويحي الرياضي التربوي دور في التقليل من صفة القلق لدى تلاميذ شهادة التعليم المتوسط. - للنشاط الترويحي الرياضي التربوي دور في التقليل من صفة الإحباط لدى تلاميذ شهادة التعليم المتوسط. - للنشاط الترويحي الرياضي التربوي دور في التقليل من صفة التوتر لدى تلاميذ شهادة التعليم المتوسط. Abstract : This study aims to reveal the relationship between recreational physical activity and psychological stress among fourth-year pupils, with an average stature of 60 students, and by using the correlational descriptive approach and by relying on the psychological stress scale, and in light of the statistical treatment of the study hypotheses to ensure their verification and non-verification, and after our analysis, presentation and discussion For the results of the study tables, we conclude that: - Physical activity, educational sports, has a role in reducing psychological pressures among intermediate education pupils. All partial hypotheses were fulfilled: - Recreational sport-educational activity has a role in reducing the anxiety characteristic of intermediate education diploma pupils. - Recreational sport-educational activity has a role in reducing the level of frustration of intermediate education diploma students. - Recreational sport-educational activity has a role in reducing the stress characteristic of intermediate education diploma pupils
MEPS-2021-15
Keywords: الكلمات المفتاحية: الترويح-المراهقة-الضغوط النفسية-النشاط الرياضي –المعالجة الإحصائية / recreation - adolescence - psychological stress - sports activity - statistical treatment.